Slope Stability Evaluation based on Empirical Methods and it’s Potential Remedy at Lesser Himalayan Zone (A Case Study of Bhalam-Hill Slope, Kaski) - Baral, Prakash (Journal of Advanced Academic Research, 2023)
The study area lies in Bhalam, Kaski district nearly 2 km from Batulechour main district road network near Gandarva community residing near Kali Khola river. The study area is comprises of several lithological factors. Field observation, sampling, lab analysis, geological survey with GPS, compass, geological hammer and tape are the main methods utilize to evaluate slope stability and possibility of failure in the study area. From the study it is found that there are few major discontinuities which play vital role in determining slope failure around the study area. The major failure due to discontinuity are planar failure, wedge failure and somewhere block failure. High ground water table approximately 0.06m, steep slope varying from 25° to 60°, improper road cutting, weathering of rock mass are major factor contributing to rock fall and landslide in the study area. The study also shows FOS